Qualitative Literature Review: The Application of The Problem-Based Learning Model in Mut'ah Marriage Education in Islamic Higher Education - Ummah, Khaira; Khadijah, Khadijah; Sari, Widya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to qualitatively review the literature on the potential and challenges of implementing the Problem-Based Learning (PBL) model in teaching the Fiqh al-Munākaḥāt course, specifically the topic of Nikah Mut'ah, in the context of Islamic Higher Education (IHE). The topic of Nikah Mut'ah is a fiqh subject rich in scholarly differences (ikhtilaf) and sensitive, requiring a pedagogical approach that can nurture critical thinking and tolerance. The method used is a qualitative literature study by analyzing academic documents, journal articles, and textbooks related to PBL, Islamic education, and contemporary fiqh. The results indicate that PBL is highly relevant for addressing the complexity and ambiguity of disputed topics, as it encourages students to construct their own understanding through analysis of real cases, comparing evidences, and producing solutions that are academically and ethically responsible. PBL facilitates the achievement of critical learning objectives and avoids dogmatism in fiqh material, with the main finding being the conceptual framework of the Adaptive Fiqh PBL Model (MPBLA-F).